Inhibitor recurrence after immune tolerance induction: a multicenter retrospective cohort study. (20th October 2015) - Antun, A.; Monahan, P. E.; Manco‐Johnson, M. J.; Callaghan, M. U.; Kanin, M.; Knoll, C.; Carpenter, S. L.; Davis, J. A.; Guerrera, M. F.; Kruse‐Jarres, R.; Ragni, M. V.; Witmer, C.; et al.
Summary: Background: Immune tolerance induction (ITI) in patients with congenital hemophilia A is successful in up to 70%. Although there is growing understanding of predictors of response to ITI, the probability and predictors of inhibitor recurrence after successful ITI are not well understood. Objectives: To determine the association of clinical characteristics, particularly adherence to factor VIII (FVIII) prophylaxis after ITI, with inhibitor recurrence in patients with hemophilia A who were considered tolerant after ITI. Methods: In this multicenter retrospective cohort study, 64 subjects with FVIII level < 2% who were considered successfully tolerant after ITI were analyzed to estimate the cumulative probability of inhibitor recurrence using the Kaplan–Meier method. The association of clinical characteristics with inhibitor recurrence was assessed using logistic regression. Results: A recurrent inhibitor titer ≥ 0.6 BU mL −1 occurred at least once in 19 (29.7%) and more than once in 12 (18.8%). The probability of any recurrent inhibitor at 1 and 5 years was 12.8% and 32.5%, respectively. Having a recurrent inhibitor was associated with having received immune modulation during ITI (odds ratio [OR] 3.8, 95% confidence interval [CI] 1.2–22.4) and FVIII recovery of < 85% at the end of ITI (OR 2.6, 95% CI 1.3–5.9) but was not associated with adherence to post‐ITI prophylactic FVIII infusion (OR 0.5, 95% CI 0.06–4.3). Conclusions: The use of immune modulation therapy during ITI and lower FVIII recovery at the end of ITI appear to be associated with an increased risk of inhibitor recurrence after successful ITI. Adherence to post‐ITI prophylactic FVIII infusions is not a major determinant of recurrence.